2020
DOI: 10.3390/molecules25081906
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing of Novel Bulk (Zr67Cu33)100−xWx(x; 5–30 at%) Glassy Alloys by Spark Plasma Sintering of Mechanically Alloyed Powders

Abstract: Metallic glassy alloys with their short-range order have received considerable attention since their discovery in 1960’s. The worldwide interest in metallic glassy alloys is attributed to their unique mechanical, physical, and chemical properties, which cannot be found together in long-range order alloys of the same compositions. Traditional preparation methods of metallic glasses, such as rapid solidification of melts, always restrict the formation of glassy alloys with large atomic fraction (above 3–5 at%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Researchers have also shown that the inclusion of a third element can improve the material characteristics. For instance, the inclusion of Al improves thermal stability [ 6 ]; the inclusion of Ta increases the hardness and Young’s modulus [ 7 ]; W improves glass transition and crystallization temperatures [ 8 ]; Ti improves corrosion resistance, electrochemical stability, and cytotoxicity [ 9 ]; and N increases hardness and enhances resistance to oxidation [ 10 ]. 304 stainless steel is an alloy material widely used in hospitals and the food industry, due to it being easy to keep clean and disinfect [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also shown that the inclusion of a third element can improve the material characteristics. For instance, the inclusion of Al improves thermal stability [ 6 ]; the inclusion of Ta increases the hardness and Young’s modulus [ 7 ]; W improves glass transition and crystallization temperatures [ 8 ]; Ti improves corrosion resistance, electrochemical stability, and cytotoxicity [ 9 ]; and N increases hardness and enhances resistance to oxidation [ 10 ]. 304 stainless steel is an alloy material widely used in hospitals and the food industry, due to it being easy to keep clean and disinfect [ 11 ].…”
Section: Introductionmentioning
confidence: 99%